Do BL Lac objects and FR I radio galaxies inhabit the same galaxy environment?. (22nd March 2019) - Sandrinelli, A; Falomo, R; Treves, A
ABSTRACT: We investigate the environments of galaxies around BL Lacertae (BL Lac) objects and Fanaroff–Riley class I (FR I) radio galaxies, the alleged parent populations of misaligned sources. We compare the environment of a sample of 50 BL Lac objects at 0.1 < z < 0.33 with that of a sample of 90 FR I galaxies at 0.1 < z < 0.15. The galaxy environment is studied by using Sloan Digital Sky Survey Data Release 14 images in the i band. We find that the galaxy excess density within 0.5 Mpc around FR I radio galaxies is a factor of ∼2 larger than that around BL Lacs. This implies a reconsideration of the parent population of BL Lac objects.